From Mentorship to Mastery: Investigating Paul's method for lay leadership formation in the early church - Sanderan, Rannu; Lilo, Deflit Dujerslaim; Sampe, Naomi (KURIOS, 2024)
The article aims is to shed light on the process of regenerating the laity into church-serving lay leaders. This article constitutes a literature review employing a qualitative approach to explore 2 Timothy 2:2, focusing on trustworthy, capable, and committed lay leadership as successors of truth. This analysis involves reading and interpreting the text 2 Timothy 2:2 while referencing relevant literature on Christian leadership and applying Paul's model of lay leadership to Timothy, aiming to contribute to developing a pattern of lay leadership for contemporary churches. This article examines the concept of lay leadership, emphasizing the leader's ability to inspire and motivate lay individuals to develop their potential and become future leaders. It underscores the importance of setting a positive example, building trust, and empowering followers to achieve change. This article employs this theory to explain how Paul mentored Timothy into a competent congregational leader for the Lord. According to the findings, Paul used a laity leadership approach to prepare Timothy for leadership in the early Christian church. He demonstrated leadership by emulating the life and attitude of the Lord Jesus. He instructed him of faith, duty, and ministry, entrusted him with ministry and leadership responsibilities, and encouraged him to be independent and mature in his leadership. Paul developed Timothy's leadership potential and prepared him to lead the Lord's congregation through this process. The conclusion emphasises the significance of transformative leadership in developing lay leaders who can effectively serve the church.Â